DAMPAK PEMBERDAYAAN RELOKASI PEDAGANG KLITHIKAN PAKUNCEN (Tinjauan Sosial â Ekonomi) - , RETNO DEWI PRAMODIA AHSANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Relocation policy is one of the measures taken by the government with the aim of seeking winwin solutions to the problems of cadger. In 2007, the City Government of Yogyakarta have started to implement the policy, and can be said to work well by moving cadgers who are in Mangkubumi street, Asem Gede street, dan Alun-alun Kidul. The purpose of the relocation is not only to maintain order and layout of the city of Yogyakarta city government, but also consider the legal aspects, aspects of empowerment, and tourist aspects. A total of 709 traders have moved, in the absence of physical violence. This is due to because the Government has entered into a dialogical approach and community participation of cadgers in each their origin place. The policy has now been running about 6 years, it has been enough to bring change. In terms of legality, the relocation policy has brought about changes the status into the formal traders, which allow them to access a bank loan or other institutions. Nevertheless, banking access is not necessarily be able to increase their income. In terms of economics, economic policy brings the dynamics of economic change on cadgers. Economic improvement is more going on cadgers that selling new goods and are able to access loans for capital increase. In contrast, the decline in income occurred on Klithikan cadgers that the actual subject of relocating. In terms of social change, the relocation of policy caused a changes in trade and kinship systems among traders. Increasing levels of competition between traders and the declining consumers causing almost no cooperation among traders in the form of goods lend to each other or lend capital. A policy that has been formulated with a variety of considerations will almost certainly not be able to satisfy all parties. There are several interest of groups that unfulfilled, and only the interests of some groups are satisfied. Almost certainly there are also unintended impact or unanticipated/expected impact, although not always be negative impact.